A tandem demetalization–desilication strategy to enhance the porosity of attapulgite for adsorption and catalysis. (17th February 2016) - Li, Xing-Yang; Zhang, Dong-Yuan; Liu, Xiao-Qin; Shi, Li-Ying; Sun, Lin-Bing
Abstract: Due to its low cost and easy availability, the natural clay, attapulgite (ATP), is a promising substitute of relatively expensive zeolites for adsorption and catalysis. However, the narrow porous network of ATP hinders its practical applications severely. In the present study, a tandem demetalization–desilication strategy was developed to enhance porosity of ATP by adding NH4 F followed the HCl treatment, for the first time. The HCl treatment leaches out the cations (including Mg, Ca, Al, and Fe) in octahedral sheets and generates silicon products, which block the pores of ATP. The subsequent addition of NH4 F leads to the formation of a buffer solution, which is efficient in the removal of silicon products. As a result, abundant secondary porosity is created, which induces an obvious increase of surface area from 128 to 232 m 2  g −1 and pore volume from 0.38 to 0.77 cm 3  g −1 . The preliminary applications of the obtained material in adsorption and catalysis were also tested. The material exhibits obviously better performance in the selective adsorption of CO2 from CH4 and N2 than pristine ATP, and the adsorption amount of CO2 increases sharply from 23.5 to 57.5 mg g −1 . In the Friedel–Crafts alkylation reaction of benzyl bromide with toluene, the obtained material can catalyze the conversion of 99.2% of benzyl bromide, which is 3.3 times as high as that catalyzed by pristine ATP. These properties make the obtained material highly promising in substituting zeolites for various applications. Highlights: A tandem demetalization–desilication strategy was developed to enhance the porosity of attapulgite. The obtained material exhibited excellent performance for selective adsorption of CO2 and catalysis. The inexpensive attapulgite may be a promising substitute of zeolite for adsorption and catalysis.